Management Information Systems Development for Sustaining Organizational Competitiveness - Ika Amelia Putri; Muhammad Irwan Padli Nasution (Yayasan Bayt Shufiya Nusantara, 2025)
The development of System Information Management (SIM) has become a strategic necessity for organizations striving to remain competitive in the digital era. As technology advances rapidly, organizations are required to manage information more efficiently to support decision making, strengthen coordination, and enhance overall performance. This study examines the development of SIM as a foundation for building agile, innovative, and competitive organizations. SIM functions not only as a tool for collecting and processing data but also as an integrated system that connects people, processes, and technology to create value. Through a qualitative approach and literature based analysis, the study highlights how well designed SIM improves operational efficiency, supports real time information flow, and accelerates managerial responses to changing environments. Furthermore, SIM enables organizations to optimize resource allocation, anticipate market trends, and meet customer expectations more effectively. The findings also emphasize that the success of SIM development depends on technological readiness, user competence, and a supportive organizational culture.